(untitled) (Journal of the College of Basic Education, 2024)
The design of fabrics and costumes within the concept of tragedy represents nothing but a documentation of events, especially the tragedies that people went through. After that, modern tragedy moved to documenting the victory of personal freedom over the laws of the institution and the state by representing human cases with designs that achieved the significance and symbolism of those cases by relying on a special vocabulary of textile and fashion designs in particular. Youth, and that is why the research problem came with the following question : ((What is the method of formal reduction in employing the concept of modern tragedy in creating designs for fabrics and fashions)) The goal of the research was also represented by ((identifying the vocabulary of modern tragedy used in the designs of fabrics and fashions)) and the first chapter dealt with the limits of the research and defining the terminology. The second chapter contained the theoretical framework on several topics, the first of which was the emergence of tragedy in the designs of fabrics and fashions and the second section was the tragedy between the constant and the variable. The third is the aesthetic organization of tragedy according to the concept of modernity. The third chapter also included the research methodology, procedures, and analysis of models. In the fourth chapter, the researcher was also able to reach the research results, which are as follows : 1-The design samples achieved compatibility with each other based on the principle of misleading shapes and the difference between shape and design space, as well as largely on the external lines. 2-The samples were able to achieve excitement and attraction through design vocabulary with a creative dimension and a human aspect that is far from minute details, thus creating a design vocabulary with a common language for all recipients This chapter also includes conclusions, recommendations and proposals